2016
DOI: 10.5860/crl.77.5.595
|View full text |Cite
|
Sign up to set email alerts
|

Health Sciences Libraries Forecasting Information Service Trends for Researchers: Models Applicable to All Academic Libraries

Abstract: To better understand the value of current information services and to forecast the evolving information and data management needs of researchers, a study was conducted at two research-intensive universities. The methodology and planning framework applied by health science librarians at Emory University and The Ohio State University focused on identifying the need for new or retooled information services supporting health and biomedical researchers and their increasing use of digital resources. The lessons lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…Assistance with open access publication generated comparatively low interest among participants, which aligned with findings by Cain et al [15]. While the majority of survey participants indicated that they were familiar with open access publishing models, only 20% regularly used these models to publish their own research (Figure 1).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Assistance with open access publication generated comparatively low interest among participants, which aligned with findings by Cain et al [15]. While the majority of survey participants indicated that they were familiar with open access publishing models, only 20% regularly used these models to publish their own research (Figure 1).…”
Section: Resultssupporting
confidence: 79%
“…Similar to studies by Hollister and Schroeder [9] and Cain et al [15], library support for funding and grant applications was ranked as very valuable by participants. From a list of 11 potential research services that the library could provide during the funding/grant application process, those ranked by participants as the most beneficial for their research were assistance in the form of a mentorship program with successful grant seekers, provision of general funder policy guidelines, and training on grant and funding databases.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Even though it was diffi cult to reveal undeniable changes in librarians' practices they defi ned themselves as more critically refl ective thinkers and felt more comfortable with research support tasks. Another noteworthy study was conducted at Emory University and Ohio State University (Cain, Cheek, Kupsco, Hartel, & Getselman, 2016). The authors identifi ed very concrete needs of academics, and they modifi ed the services offered by the library to fi t them.…”
Section: Research Support: Practicesmentioning
confidence: 99%
“…We need to collaborate from the start to plan research that is applicable to multiple libraries, such as a recent study looking at the evolving needs of researchers in information and data management (Cain, Cheek, Kupsco, Hartel, & Getselman, 2016). The authors hope to develop new information service models that can be used by others, based on surveys conducted at two research-intensive universities.…”
Section: Figures 3 and 4)mentioning
confidence: 99%